Integrating High Impact Practices: Recognizing Attributes and Overcoming Obstacles in Learning ePortfolios - Rivera , Jeno; Loebick, Karla (Experiential Learning and Teaching in Higher Education, 2022)
In the era of educational accountability, the push to document and demonstrate student learning increases exponentially. Creating opportunities for students to evidence their learning and, more broadly, the value of a college education, is critically important to both internal and external higher education stakeholders. While ePortfolios are an increasingly common tool used to provide evidence of learning, little is known about their effectiveness in assessing integrated learning experiences. The Bailey Scholars Program, an interdisciplinary, self-directed, student-centered learning community at Michigan State University, fosters creativity among faculty and students. The program explores innovative approaches to documenting and assessing learning that are responsive to student needs for life after the program while also being attentive to the uniqueness of a self-directed learning environment. One approach taken by the program is the community-wide use of ePortfolios. In this article, we argue that learning ePortfolios are a high impact practice that has the potential to change the ways students and programs partner to demonstrate and document student learning. We identify issues to take into account when adopting ePortfolio technology, and we include discussion of the attributes of ePortfolios that document both the learning and the obstacles students face while they are using ePortfolios.